Short-coupled variant of torsade de pointes: A systematic review of case reports and case series - Wang, Guangqiang; Zhong, Lin; Chu, Hongxia; Wang, Chunxiao; Zhu, Xuefeng (Frontiers in Cardiovascular Medicine, 2022)
Background: The short-coupled variant of torsade de pointes (scTdP) is characterized by a particular electrocardiogram (ECG) pattern that shows a short-coupling interval of the initial Tdp beat and that can degenerate into ventricular fibrillation without the presence of structural heart disease. However, its etiology, epidemiology, clinical characteristics, underlying mechanism, treatment, and prognosis remain unclear. This study aimed to systematically review case reports and series of scTdP to synthesize existing data on the demography, clinical characteristics, ECG features, management, and outcomes. Methods: A literature search was conducted for eligible published articles using the Medline, Embase, and PubMed databases. All eligible case reports and case series were included without any language restrictions. SPSS 24 was used for statistical analysis. Results: A total of 22 case reports and 103 case series of patients with scTdP were identified and included in the analysis. All selected cases had acceptable quality of evidence. Most young patients without sex differences had no trigger or a negative programmed simulation. The ECGs of all selected patients showed a short first-coupling interval (302±62 ms) and a long QRS duration of ventricular extrasystole (VE) (135±17 ms). The first coupling interval levels and QRS duration levels of VE were significantly longer and wider in patients with scTdP originating from the right ventricular outflow tract (RVOT) than in those with scTdP originating from the Purkinje fibers (380±70 vs. 274±28 ms, P < 0.001; 147±8 vs. 131±17 ms, P < 0.001), respectively. The receiver operating characteristic curve showed that the optimal cutoff values of the first coupling interval triggering TdP and QRS duration of VE were more than 319 ms and 141 ms (92% sensitivity, 95.7% specificity; 82.6% sensitivity, 77.8% specificity) for predicting the RVOT origin, respectively. The Kaplan-Meier survival curve revealed increased survival in patients with implantable cardioverter defibrillator (ICD) implantation than in patients without ICD implantation (log-rank =10.127, P = 0.001). Conclusion: Some agreements were confirmed in selected case reports regarding the clinical features, diagnosis, and management of scTdPs. Further large-scale and long-term follow-up studies are required to clarify the existing arrhythmogenic entities.